CHARACTER ASSOCIATION AND PATH COEFFICIENT ANALYSIS FOR SEED YIELD AND ITS CONTRIBUTING TRAITS IN SOYBEAN [GLYCINE MAX (L.) MERRILL] - DINESH KUMAR THAKUR; SUNIL KUMAR NAG; TULESH KUMAR GENDLEY; RAKESH KUMAR PATEL (The Bioscan, 2015)
An experiment was conducted with forty genotype of soybean (Glycine max (L.) Merrill.), to study character association among the seed yield contributing traits and their direct and indirect effects on the seed yield. Correlation studies indicated that out of 12 characters, seed yield per plant showed significant positive correlation with pod bearing nodes (0.578), number of pods per plant (0.397), number of seeds per pod (0.368) and 100 seed weight (0.471). Path coefficient analysis showed that, pod bearing length (3.999) contributed most directly to seed yield among all the traits whereas, other characters like, number of pods per plant (3.173), number of seeds pod -1 (1.514),100- seed weight (1.039) and oil content (2.003) both directly and indirectly influenced seed yield.Therefore, this is suggested that the traits viz., number of pods per plant, number of seeds per pod and 100 seed weight and pod bearing lengthmay be considered as important traits during theselection for improvement of seed yield in soybean.